في تعليم المفردات لدروس اللغة العربية في الفصل الأول بالمدرسة المتوسطة (Wordwall) فعالية استخدام وسيلة وورد وول - Dedi Mulyanto; Fairuzah; Amir Hadif Bin Amir Suhaimi (Program Studi Pendidikan Bahasa Arab, 2024)
Vocabulary mastery is a fundamental step in learning Arabic, as it significantly influences overall language proficiency. According to Hanifah Nur Azizah, language skills develop in proportion to vocabulary acquisition. This study was conducted at Al-Tibyan Islamic Boarding School in Banten, where first-grade students demonstrated low proficiency in Arabic due to limited vocabulary comprehension. Students often struggled to recall the meanings of vocabulary taught or written on the board, which negatively affected their test performance. The lack of effective teaching tools—attributed to the institution's relatively recent establishment—further hindered the learning process. To address this issue, the researcher implemented Wordwall media as a vocabulary teaching tool. The objectives of this study were: (1) to describe the use of Wordwall media in teaching Arabic vocabulary, and (2) to determine its effectiveness in enhancing vocabulary acquisition among first-grade students. The study employed a quasi-experimental design using a pretest-posttest control group method. A total of 22 students were divided into experimental and control groups, with 11 students in each. Data were collected through vocabulary tests administered before and after the intervention. The results showed that the experimental group's average score increased from 09.29 (pre-test) to 36.56 (post-test), while the control group's score rose from 31.82 to 40.00. Statistical analysis using the Mann-Whitney U test revealed a significance value of 0.000 (p < 0.05), indicating a significant difference between the two groups. Thus, the null hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was accepted. The findings conclude that Wordwall media is effective in teaching vocabulary in Arabic language lessons. It is recommended that this tool be more widely adopted in Arabic language instruction to enhance learning outcomes.